How to be a good Muslim — practical wisdom drawn from the kitabs of the Grand Duchy of Lithuania Tatars (on the basis of the Kitab of Ivan Lutskevich) - Konopacki, Artur (Slavistica Vilnensis, 2016)
The following article raises a subject of moral teaching which can be found in Muslims’ holy books of the Grand Duchy of Lithuania. Those Muslims living among Christians were made to create their own religious literature in order to maintain their religion of Islam. Kitab was a specific compendium of religious knowledge. It contains all orders and prohibitions of religious nature. Kitab was a source of information especially for Muslims living away from the Muslim world who looked for guidance how to treat their brothers and neighbouring Christians. Kitab enlists warnings and descriptions of different forms of punishment given to Muslims who refuse to obey the given guidelines. Kitab also has a lot of references and quotations from Koran. What is essential from the researcher’s point of view is the fact of interfusion of Islamic religion with elements and local beliefs of infernal punishment. Kitab is an incredibly interesting form of religious manuscript of Tatar people living in the Grand Duchy of Lithuania.
Keywords: Tatars of Grand Duchy of Lithuania; Muslims; kitab; kitabistika; Koran; Łuckiewicz; moral teaching; Islam; Muslims’ holy books